Field environmental philosophy: ecology and ethics in LTSER-Chile and ILTER networks - Rozzi, Ricardo; Massardo, Francisca; Contador, Tamara; Crego, Ramiro D; Méndez, Manuela; Rijal, Rajan; Cavieres, Lohengrin A; Jiménez, Jaime E (BOSQUE, 2017)
The long-term socio-ecological research (LTSER) study sites should integrate theoretical and applied research to effectively confront global socio-environmental change. For a socio-ecological integration beyond the socio-economic approach that prevails today in LTSER networks worldwide, in the southernmost site of the LTSER-Chile network (Omora Park, 55o S) we have developed the Field Environmental Philosophy (FEP) methodological approach. This paper presents a methodological framework and applications of FEP at Omora Park that combine ecological and philosophical research in education and biocultural conservation programs, including ecotourism. Through in situ and in tempo work with educators, policy makers and other stakeholders, researchers not only investigate the relations between society and ecosystems, but also transform them. This ecological and ethical understanding orient educational and governance processes toward ecological, socio-cultural and economic sustainability. The experiences of FEP demonstrate how this methodology transforms socio-ecological relationships by: (i) changes in language that generate in society a "change of lenses" to appreciate values and the symbolic-linguistic reality, usually studied by philosophers; this change determines, in turn, (ii) transformations in the ways in which society understands and value the biophysical reality of ecosystems, usually studied by ecologists. Globally, the FEP provides a methodology that contributes to orient global society towards ways that better understand and value biodiversity, favoring the sustainability of life.